American Industrial Policy - Nester, William R. author. aut Link
V, 288 p.
Keywords: What is the government's proper role in the economy? Do free or managed markets best promote economic development? Who can best pick industrial winners and losers, the government or private sector? This book attempts to answer those and related questions by exploring the evolution and results of federal policies towards half a dozen economic sectors. Those policies are largely determined by the representatives of the targeted industry, bureaucrats from agencies and departments that administer that industry, and politicians with firms from that industry in their districts. These 'iron triangles' capture a 'virtuous' political economic cycle in which they use their united power to grant themselves favourable policies which in turn enhances their power. As will be seen, the results of such a politicized industrial policy process varies considerably from one industry to the next.